Inventarisasi Jenis Paku-Pakuan (Pteridophyta) di Hutan Sebelah Darat Kecamatan Sungai Ambawang Kalimantan Barat - Elvi Rusmiyanto P.W., Hotmatama Hasibuan, Rizalinda, (Universitas Tanjungpura, 2016)
Ferns (Pteridophyta) as a plant community in biodiversity has important ecological function in forest ecosystems and human living. The human activities on the forest may lead to ecosystems disruption and reducing natural resources preservation, including reducing ferns species in the forest. Inventory of ferns species need to be performed to gathering information for the preservation and development of the region. The research was conducted from Juni 2015 to September 2015. Ferns sampling was performed on Sebelah Darat, Lingga Village Forest, Sungai Ambawang District. Cruise method was employed to collect ferns. The results were obtained showing that there are 20 kinds of epiphytic and terrestrial ferns dividing of 11 families, Aspleniaceae, Blechnaceae, Davalliaceae, Dennstaedtiaceae, Lindsaeaceae, Lycopodiaceae, Lygodiaceae, Polypodiceae, Gleicheniaceae, Pteridaceae and Selaginellaceae.